Alterations in Signal Dynamics during Regulation of Airway Reflex Response - Juliana Knocikova (Communications - Scientific letters of the University of Zilina, 2010)
Regulatory airway mechanisms were studied on the basis of phrenic nerve activity which was compared during eupnea and aspiration reflex (AspR). Due to changing degrees of signal stationarity, discrete wavelet transformation enabling multiresolution analysis was performed, followed by calculation of wavelet energy and wavelet entropy parameters.The higher rate of wavelet energy was detected in lower frequency components during AspR in contrast to eupnea. Moreover, quiet inspiration is characterized by higher wavelet entropy comparing to the AspR, indicating the probability of its random character and varying degree of system disorder during transient between different respiratory responses.